A faster optimal model slotting in rack positions with mono SKU pallet (2022)
The warehouse, with its racking positions, oversees regulate the flow of goods in the distribution center (DC). An adequate distribution of the products in the warehouse (slotting), reduces the operating picking times once is done by a full pallet. This paper presents a mathematical model that optimizes slotting times in a selective shelving and random storage warehouse. The model places the products with the highest turnover rate and ABC inventory valuation close to the dispatch area. In addition, it places high-value products on the upper shelf levels and heavy pallets on the lower levels. The results applied to a company dedicated to the manufacture of cellulose pulp and derivatives, obtained a 19.24% reduction in operating time.